EFL Students’ Engagement in Reading Classroom by Using Story-Mapping - Putri, Ashrini Syafira; Nugraha, Sidik Indra; Ridwan, Iwan (English Education Department, Postgraduate, Universitas Sultan Ageng Tirtayasa, Indonesia, 2024)
Reading comprehension of EFL students have been concern of scholars by researchers, they have low motivation, interest and participation in the process of reading comprehension. Due to this problem, teacher should choose a suitable strategy to teach reading comprehension especially in narrative text reading. This study is aimed at investigating how students are engaged in reading cllassroom by using story-mapping technique. The study used a case study as a qualitative research design, involving ninth grade students at Junior High School in Cibitung as participants. The data were collected through observation and interview. The findings showed that EFL students’ engagament in learning reading narrative text by using story map technique resulted in three types, namely cognitive engagement, emotional engagament, and behavioral engagement. The story map can help students learn to read narrative text in a cognitively. Furthermore, students exhibit positive reactions as well as emotional engagement with the story mapping technique. Finally, students who engage in behavioral engagement actively participate in the learning process